Determinants of Information Technology Investment Expenditure - Josua Panatap Soehaditama; Adler Haymans Manurung; Nera Marinda Machdar; Wastam Wahyu Hidayat (Greenation Research & Yayasan Global Resarch National, 2025)
Amid globalization, financial deregulation, and market volatility, banks aggressively adapt to maintain long-term competitive advantages. While digital transformation is non-negotiable, heavy capital allocations for Information Technology (IT) often face the